Ascendobifemoral Bypass for the Treatment of a Thoracic Endograft Infection - Pleger, Sebastian Paul; Nink, Nadine; Böning, Andreas; Koshty, Ahmed (The Thoracic and Cardiovascular Surgeon Reports, 2017)
Background Endograft infections (EIs) are rare complications after endovascular procedures in the thoracic and abdominal aortas. The challenging treatment encloses antibiotic and surgical therapies.Case Description A 74-year-old male patient developed an EI after an endovascular procedure (thoracic endovascular aortic repair [TEVAR]). Despite a long-term oral antibiotic therapy, the clinical symptoms showed no falling trend. Because of the expanded infection from above the celiac trunk up to the aortic arch, we decided to remove the infected endograft and to implant an extra-anatomic ascendobifemoral bypass.Conclusion The implantation of an ascendobifemoral bypass was a successful treatment option for EIs after TEVAR.
Keywords: endograft infection; TEVAR; ascending aorta; ascendobifemoral bypass; extra-anatomic; revascularization